KLF2 Mediates the Suppressive Effect of Laminar Flow on Vascular Calcification by Inhibiting Endothelial BMP/SMAD1/5 Signaling. Issue 4 (23rd June 2021) - Huang, Juan; Pu, Yujie; Zhang, Hongsong; Xie, Liping; He, Lei; Zhang, Cheng-Lin; Cheng, Chak Kwong; Huo, Yingsong; Wan, Song; Chen, Shaoliang; Huang, Yuhong; Lau, Chi Wai; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Vascular calcification in arterial intima is closely associated with atherosclerosis. Endothelial cells (ECs) sense blood flow and respond to the mechanical cues generated by different flow patterns. Laminar flow induces an anti-atherosclerotic EC phenotype whereas disturbed flow exerts an atheroprone effect. However, the contribution of blood flow to calcification in atherosclerotic arteries remains to be evaluated. Objective: We aim to investigate whether blood flow plays a determinant role in the distribution of vascular calcification and the underlying mechanisms involved. Methods and Results: Computed tomography angiography analysis of human coronary arteries (n=48) shows that calcification preferentially develops at flow perturbated sites. Similar phenomenon was observed in calcified human aortic valves and mouse arteries. Nonuniform shear stress produced in Y-shaped slide simulating live conditions in branched arteries promotes calcification in human umbilical vein ECs. The expression of KLF2 (Krüppel-like factor 2), a transcription factor inducible by laminar flow, is reduced in ECs of calcified human aortic valves and in endothelial calcification model, suggesting that KLF2 downregulation is likely involved in intimal calcification. Indeed, KLF2 silencing induces endothelial-to-mesenchymal transition and accelerates osteoinduction in both human aortic ECs and human umbilical vein ECs. EC-specific KLF2 knockdown promotes whereas AAV9 (adeno-associated virus serotype 9)-mediated EC-KLF2 overexpression ameliorates vascular calcification in ApoE −/− mice. Global mRNA profiling in human umbilical vein ECs reveals that KLF2 inhibits the BMP (bone morphogenetic proteins)/SMAD1/5 pathway which is critical in vascular calcification. Furthermore, KLF2 mediates laminar flow-induced inhibition of the BMP/SMAD1/5 pathway. By contrast, disturbed flow-induced activation of BMP/SMAD1/5 pathway is suppressed by KLF2 overexpression. Mechanistically, KLF2 binds to the promoters of BMP4, BMPER, and SMAD1 to directly regulate their expression in ECs. Conclusions: Vascular calcification prefers to occur at branched or bifurcated areas of vasculature. Laminar flow inhibits vascular calcification through KLF2-mediated inhibition of endothelial BMP/SMAD1/5 signaling. Targeting KLF2 may represent a novel therapeutic approach against vascular calcification.